Human Resource Management in a Syari’ah Economic Perspective - Dwi Vita Lestari Soehardi; Satriadi Satriadi; Chintia Hendryeni; Dwi Khoirun Nisah; Chika Juliana Putri (Journal of Islamic Economy, 2024)
The majority of Indonesia's population is Muslim, making it necessary to have designs that consider religious aspects in increasing efficiency and harmony in organizations. This research aims to review how human resource management is viewed from a sharia economic perspective. The research method used was qualitative research with data collection carried out through literature study (library). The research results show that Human Resources Management (HR) in the context of sharia economics has a significant positive impact on organizations and employees. Based on the principles of the Koran and Hadith, this management increases employee responsibility, integrity and trust. Islamic values such as honesty, justice, transparency, and a passion for self-improvement motivate employees to work with full commitment, increase productivity, and strengthen loyalty to the organization. Overall, the application of sharia principles in HR management not only provides benefits in improving organizational performance and efficiency, but also has a positive impact on the spiritual and moral welfare of employees and creates a harmonious, productive and ethical work environment.